Frequencies of psychiatric morbidities identified in employees of public sector organizations presented to psychiatric services - Afridi, Muhammad Iqbal; Lal, Chooni; Khan, Saba; Khan, Zarwali; Hanif, Rida; Badar, Ammara (Journal of Pakistan Psychiatric Society, 2019)
ABSTRACT